Biological and chemical composition of pomegranate fruit grown in Azerbaijan and Uzbekistan - Bobayev Isomiddin Davronovich; Niyozov Xasan Niyoz o’g’li; Maxmadqulova Kumush Furqat qizi; O’rinboyev Javoxir Jahongir o’g’li; Xakimov Asilbek Islom o’g’li (Zien Journals, 2022)
In the collections, 69 varieties of pomegranate were taken into account. But in farms specializing in Uzbekistan are planted mostly bitter and Kazakh pomegranate lot, picky pomegranate, red pomegranate, white pieces, ulfi and b. varieties are also widely scattered
Keywords: Uzbekistan; Azerbaijan; leaves; pomegranate